Rhetoric and international relations - Salazar, Philippe Joseph (Javnost (Ljubljana), 2005)
A rhetorical interpretation of international relations and conflicts necessitate to take into consideration three main aspects of what anthropologist Mauss called "international life" - cultural features that allow human groupings to argue with one another across borders. The first aspect concerns the instability of international glossaries to instrument diplomacy; the second aspect is the pre-conceived notion that peace, or non-conflicting "relation," is a normal state for arguing among nations; the third aspect pertains to the belief that, owing to globalisation, the same modes of persuasion operate indiscriminately. The French Revolution provides an excellent illustration of all three aspects.
Keywords: mednarodni odnosi; komuniciranje; communication; diplomacija; diplomacy; retorika; rhetoric; globalizacija; globalization